ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TH. 2009 – 2010 - DARSONO DARSONO (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2014)
This research has the aim to (1) examine the effect of profitability on capital structure (2) examine the effect of asset structure of moal structure (3) test the effect of sales growth of capital structure (4) examined the effect of firm size on capital structure. The research was conducted at a manufacturing company listed on the Indonesia Stock Exchange the period 2009 to 2010 period. Sampling technique with the purposive sampling method. In selecting the sample is fully based on the researcher's own judgment regarding the completeness, clarity of data, and the availability of data. To analyze the data used regression analysis, t test, and F test. The results of regression analysis found that of the studied variables known emapat ROA negative influence on capital structure. While the variable structure of assets, sales and company size pertubuhan positive effect on capital structure in the Indonesia Stock Exchange. Based on the coefficient of determination (R2) which has a positive value of 0.361 which indicates that the manufacturing capital structure listed on the Stock Exchange can be explained by factors ROA, asset structure, firm size and sales growth of 31.60% and the balance of 68.40% described the existence of free variation (independent variables) that are not observed in this study (external factors). Â